KNOWLEDGE AND USE OF ORAL REHYDRATION THERAPY AMONG MOTHERS OF UNDER-FIVE CHILDREN IN ODOGBO ARMY BARRACKS, IBADAN, NIGERIA (2012)
Diarrhoeal diseases constitute a major cause of morbidity and mortality among under-five children in Nigeria. The knowledge and use of home therapies to manage diarrhoea using Oral Rehydration Therapy (ORT) with special reference to Sugar-Salt-Solution (SSS) are on the decline in recent times. However, knowledge and self-efficacy of nursing mothers in Nigerian army barracks relating to the use of ORT have not been fully studied. The study was designed to assess the knowledge of diarrhoea and ORT and identify diarrhoea management practices involving use of SSS among mothers of under-five children in Odogbo army barracks, Ibadan. A two-stage random sampling technique was used to select 403 mothers in Odogbo army barracks. A validated semi-structured questionnaire was used for data collection. The questionnaire included an 18-point diarrhoea knowledge scale and an 11-point ORT/SSS knowledge scale. Diarrhea knowledge scores of 0-8, 9-13 and 14-18 were rated as poor, fair and good while the ORT/SSS knowledge scores of 0-4, 5-7 and 8-11 were considered poor, fair and good respectively. Data were analyzed using descriptive statistics and Chisquare with level of significance set at 0.05. The mean age of respondents was 29.8 ± 5.5 years, most (99.3%) were married and 63.0% were Christians. The occupations of respondents included petty-trading (43.0%), full-time “housewives” (35.7%) and artisans (12.9%). Most respondents (98.0%) were aware of ORT, 95.0% correctly stated the composition of SSS and 43.9% were able to state the correct proportions of sugar, salt, and water in SSS. Respondents‟ sources of information about ORT included health personnel (78.7%), relatives (11.4%) and television (6.0%). The listed causes of diarrhoea included teething (51.7%) and dirty environment (29.0%). Diarrhoea was perceived by 46.0% to be a serious health condition. Respondents‟ mean knowledge score on diarrhoea was 13.3 ± 2.4 while the mean knowledge score on ORT/SSS was 7.6 ± 1.8. The mean knowledge score on diarrhoea among mothers aged < 25 years was 12.3 ± 2.8 while the mean score among those aged ≥ 25 years was 13.5 ± 2.3 with no significant difference. Mean knowledge score on ORT/SSS among mothers aged <25years was 6.9 ± 2.3 while the mean score among those aged ≥25years was 7.7 ± 1.6 with no significant difference. Majority (79.9%) of respondents reported that, children had diarrhoea within the three months preceding the study and home treatment given included use of ORT (49.5%), other orthodox medicines (22.6%) and native medicine (3.7%). Seventy percent of respondents stated that they could prepare SSS, but 72.7% preferred taking children with diarrhoea to the hospital instead of using SSS. Forty-nine percent of the respondents were of the view that cleanliness of the environment was one of the preventive measures against childhood diarrhoea. Knowledge about diarrhoea diseases and oral rehydration therapy was high among respondents, but their use of oral rehydration was low. Training, public enlightenment and social marketing strategies are needed to promote the use of oral rehydration therapy among nursing mothers